Yeast cell templated porous hollow silica spheres for rapid hemostasis accompanied by antibacterial action. (14th March 2023) - Shi, Yuting; Fang, Yu; Liang, Xiaoqin; Huang, Congshu; Liang, Yu; Yang, Zheng; Yu, Jianping; Wang, Jianrong; Zhao, Guanghui
Abstract : This work aims to prepare a dual-function composite material Ag@HMSN with integrating hemostasis and antibacterial effects in situ by simulating the chemical composition of diatomite using yeast. Abstract : Uncontrolled haemorrhage is the leading cause in nearly 91% of pre-hospital deaths, which were considered potentially survivable. In particular, severe trauma is susceptible to infection, which further affects the natural healing process and can even lead to life-threatening sepsis. Therefore, we established Ag@HMSN nanocomposites based on a yeast cell template that combines hemostasis with antibiosis and further studied the effects of different calcination temperatures on the hemostatic and antibacterial properties. From the experimental results, Ag@HMSNs/500 shows excellent bactericidal effect on a mouse skin infection model and outstanding hemostatic effect on a mouse liver injury model, which could be used as the next-generation hemostatic and antibacterial material.